Design and Implementation of BHN Testing Equipment To Measure Remaining Stress Of Wheelset Parts (Tie Rod and Stabilizer Bar) - Balogh, Gábor; da Silva, Lucas Pereira (International Journal of Engineering and Management Sciences, 2020)
Nowadays in the automotive industry both production and service, requires accurate lifetime calculations. Today we have big amount of theoretical background and nowadays the importancy of technical and industrial databases become more and more important. By materials scientific and fracture mechanics aspects are well covered, but the remaining stresses which are present in every step of production, we can not clearly identify the origin of them. There are different paralell methods to mesure them, but the application of different methods are depending on the engineers, and their expreiences at the company. This part of the analysis is not standardised yet, so there are differences even in the same company.